Keroncong Ambyaran”: Inovasi dalam Pembawaan Keroncong oleh Keroncong Syahdu di Semarang - Khoiruddin, Nur Faqih Imam; Abdul Rachman, S.Pd, M.Pd (Universitas Negeri Surabaya, 2025)
Keroncong music, as one of Indonesia's cultural heritages, is often considered outdated by the younger generation. However, the development of contemporary music presents opportunities to revitalize this genre. This article explores the innovation of